A New Stoicism - Becker, Lawrence C. (Book collections on Project MUSE., 2001)
What would stoic ethics be like today if stoicism had survived as a systematic approach to ethical theory, if it had coped successfully with the challenges of modern philosophy and experimental science? A New Stoicism proposes an answer to that question, offered from within the stoic tradition but without the metaphysical and psychological assumptions that modern philosophy and science have abandoned. Lawrence Becker argues that a secular version of the stoic ethical project, based on contemporary cosmology and developmental psychology, provides the basis for a sophisticated form of ethical na.